2013
DOI: 10.1002/adsc.201300524
|View full text |Cite
|
Sign up to set email alerts
|

First Tandem Asymmetric Conjugate Addition of Alkenyl Nucleophiles and Silyl Trapping of the Intermediate Enolates

Abstract: The tandem asymmetric conjugate addition of alkyl or aryl groups to enones and subsequent silyl trapping has already been achieved and yields valuable silyl enol ethers. Herein, the first method for the respective addition of alkenyl groups is reported, which is based on a rhodium(I)‐catalyzed addition of readily available alkenylzirconocenes. As prerequisite for silyl trapping, the initially formed enolates have to be transmetalated from zirconium to lithium by treatment with methyllithium prior to addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…The closest precedent for a catalytic reaction that results in the regio- and stereoselective synthesis of a silyl enol ether involves a Rh(L*)-catalyzed enantioselective conjugate addition (Scheme 1) of an alkenylorganozirconium reagent to a cycloalkenone ( 1 ) followed by a difficult (large excess of 4 reagents, long reaction times) in situ silylation of the weakly reactive zirconium-enolate 2 (see step 2). 3a The reaction shows poor selectivity for the preparation of acyclic derivatives (e. g., 4 ). 3b While similar catalytic asymmetric conjugate alkenylation of enones using alkenyl boronates 4a,b and alkenyl aluminum reagents 4c,d are known, no such reaction has been reported for simple vinyl (H 2 C=CH-) additions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The closest precedent for a catalytic reaction that results in the regio- and stereoselective synthesis of a silyl enol ether involves a Rh(L*)-catalyzed enantioselective conjugate addition (Scheme 1) of an alkenylorganozirconium reagent to a cycloalkenone ( 1 ) followed by a difficult (large excess of 4 reagents, long reaction times) in situ silylation of the weakly reactive zirconium-enolate 2 (see step 2). 3a The reaction shows poor selectivity for the preparation of acyclic derivatives (e. g., 4 ). 3b While similar catalytic asymmetric conjugate alkenylation of enones using alkenyl boronates 4a,b and alkenyl aluminum reagents 4c,d are known, no such reaction has been reported for simple vinyl (H 2 C=CH-) additions.…”
mentioning
confidence: 99%
“…3a The reaction shows poor selectivity for the preparation of acyclic derivatives (e. g., 4 ). 3b While similar catalytic asymmetric conjugate alkenylation of enones using alkenyl boronates 4a,b and alkenyl aluminum reagents 4c,d are known, no such reaction has been reported for simple vinyl (H 2 C=CH-) additions. In all these cases, the products of addition are almost invariably the ketones, and not the more synthetically useful, regioselectively trapped enolates.…”
mentioning
confidence: 99%
“…Hoveyda's allylic alkylation. [57] Treatment of the zirconium enolatei nitially produced in the reaction with an excesso fM eLi at À78 8Cg ives al ithiume nolate which can be trapped as as ilane. [56] More recently,Z ezschwitz et al reported addition of alkenylzirconocenes followed by silyl trapping to give silylenol ethers (Scheme 20).…”
Section: Aca Initiated Using Nucleophiles Generated By Hydrozirconationmentioning
confidence: 99%
“…[56] More recently,Z ezschwitz et al reported addition of alkenylzirconocenes followed by silyl trapping to give silylenol ethers (Scheme 20). [57] Treatment of the zirconium enolatei nitially produced in the reaction with an excesso fM eLi at À78 8Cg ives al ithiume nolate which can be trapped as as ilane. The reactioni s quenched with au rea-hydrogen peroxide adduct, which allows isolation of the enol-silane.…”
Section: Aca Initiated Using Nucleophiles Generated By Hydrozirconationmentioning
confidence: 99%